Ultrasonography validation for early alteration of diaphragm echodensity and function in the mdx mouse model of Duchenne muscular dystrophy. - Antonietta Mele; Paola Mantuano; Adriano Fonzino; Francesco Rana; Roberta Francesca Capogrosso; Francesca Sanarica; Jean-Francois Rolland; Ornella Cappellari; Annamaria De Luca (PLoS ONE, 2021)
The mdx mouse model of Duchenne muscular dystrophy is characterized by functional and structural alterations of the diaphragm since early stages of pathology, closely resembling patients' condition. In recent years, ultrasonography has been proposed as a useful longitudinal non-invasive technique to assess mdx diaphragm dysfunction and evaluate drug efficacy over time. To date, only a few preclinical studies have been conducted. Therefore, an independent validation of this method by different laboratories is needed to increase results reliability and reduce biases. Here, we performed diaphragm ultrasonography in 3- and 6-month-old mdx mice, the preferred age-window for pharmacology studies. The alteration of diaphragm function over time was measured as diaphragm ultrasound movement amplitude. At the same time points, a first-time assessment of diaphragm echodensity was performed, as an experimental index of progressive loss of contractile tissue. A parallel evaluation of other in vivo and ex vivo dystrophy-relevant readouts was carried out. Both 3- and 6-month-old mdx mice showed a significant decrease in diaphragm amplitude compared to wild type (wt) mice. This index was well-correlated either with in vivo running performance or ex vivo isometric tetanic force of isolated diaphragm. In addition, diaphragms from 6-month-old dystrophic mice were also highly susceptible to eccentric contraction ex vivo. Importantly, we disclosed an age-dependent increase in echodensity in mdx mice not observed in wt animals, which was independent from abdominal wall thickness. This was accompanied by a notable increase of pro-fibrotic TGF-β1 levels in the mdx diaphragm and of non-muscle tissue amount in diaphragm sections stained by hematoxylin & eosin. Our findings corroborate the usefulness of diaphragm ultrasonography in preclinical drug studies as a powerful tool to monitor mdx pathology progression since early stages.